Digital Control of Static Var Compensator with Field Programmable Gate Array - Ram Shankarrao Dhekekar; N. V. Srikanth (International Journal of Reconfigurable and Embedded Systems (IJRES), 2012)
This paper is about real time simulation and implementation of FPGA Digital Control of Static VAR compensator for 750km lab model of artificial transmission line. In this paper, a new method of controlling SVC using Field Programmable Gate Array (FPGA) is suggested. FPGA controller is used to generate the firing pulses required to for Static Var Compensator. Pulses are synchronized with AC input; the delay of pulses determines the firing angle to driver circuit. The proposed control scheme has been realized using XILINX FPGA SPARTAN 2 XC2S200 and tested actual testing proves that these devices when installed, they keep the bus voltage same as reference voltage (sending-end voltage). The results are prominent and give a way for real-time implementation of the proposed control schemes. These control schemes are simulated for the real-time control along with real-time modeling and simulations.The results are prominent and give a way for real-time implementation